Human liver stem cells improve liver injury in a model of fulminant liver failure12. Issue 1 (7th January 2013) - Herrera, Maria Beatriz; Fonsato, Valentina; Bruno, Stefania; Grange, Cristina; Gilbo, Nicholas; Romagnoli, Renato; Tetta, Ciro; Camussi, Giovanni
Abstract Liver transplantation is currently the only effective therapy for fulminant liver failure, but its use is limited by the scarcity of organs for transplantation, high costs, and lifelong immunosuppression. Here we investigated whether human liver stem cells (HLSCs) protect from death in a lethal model of fulminant liver failure induced by intraperitoneal injection of D‐galactosamine and lipopolysaccharide in SCID mice. We show that injection of HLSCs and of HLSC‐conditioned medium (CM) significantly attenuates mouse mortality in this model. Histopathological analysis of liver tissue showed reduction of liver apoptosis and enhancement of liver regeneration. By optical imaging we observed a preferential localization of labeled HLSCs within the liver. HLSCs were detected by immunohistochemistry in large liver vessels (at 24 hours) and in the liver parenchyma (after day 3). Fluorescence in situ hybridization analysis with the human pan‐centromeric probe showed that positive cells were cytokeratin‐negative at 24 hours. Coexpression of cytokeratin and human chromosome was observed at 7 and, to a lesser extent, at 21 days. HLSC‐derived CM mimicked the effect of HLSCs in vivo. Composition analysis of the HLSC‐CM revealed the presence of growth factors and cytokines with liver regenerative properties. In vitro experiments showed that HLSC‐CM protected human hepatocytes from apoptosis and enhanced their proliferation. Conclusion: These data suggest that fulminant liver failure may potentially benefit from treatment with HLSCs or HLSC‐CM. (HEPATOLOGY 2013)